Innovation Readiness Analysis of Battery Electric Vehicle: A Case of Gesits G1 - Habiburrahman, Rais; Ulkhaq, M. Mujiya (Proceeding International Conference on Religion, Science and Education, 2024)
Battery Based Electrical Vehicle development’s urgency in Indonesia is for improvement, efficiency, and energy conservation in transportation sector and to actualize clean energy and air, as well as the nation’s commitment to reduce greenhouse gas emission. The biggest challenge these vehicle products faced are competitors from giant markets such as China and Japan as well as the procurement of the main component which still rely heavily on import, hence the need for the Innovation Readiness Levels (IRL) to give answer to innovation development with an effective cycle. Innovation Readiness Levels is a framework used to identify, evaluate, and measure an organization's readiness level in adopting and implementing innovation. Six points in innovation includes concept, components, completion, chasm, competition, and changeover/closedown. The identification results shows that the innovation readiness in KATSINOV 5 reaches 75, 83% as well as on the measurement aspects of IRL, the market aspect have a lowest KATSINOV of 65, 71%, while the partnership, risk, and technology have the biggest KATSINOV level of 80%, hence it is classified in the IRL measurement did not reach the minimum limit and so improvement is needed in every aspect. Finally, the recommendation given is for effectivity improvement, organization cooperation, and also product differentiation and partnership to increase the competition in the market.